This living planet - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
World atlas of biodiversity. Earth s living resources in the 21st century By B Groombridge and M D Jenkins, UNEP, 2002. 339 pp. ISBN 0520236688 Stock number: 3114 US$ 54.95 Euro 53.35